Ethos Amerika : sikap masyarakat terhadap kapitalisme dan demokrasi - Mc Closky, Herbert; Zaller, John ; Sarjono, J.F.R. ; Rambadeta, Alex H. (Gadjah Mada University Press, 1988)
xxii, 516 hlm. : ilus. ; 21 cm.